Heteroptera (Insecta) fauna of Iranian cotton fields and surrounding grasslands - Ghahari, Hassan (2011)
The Heteroptera fauna (Insecta) of Iranian cotton fields and surrounding areas is studied. A total of 103 species from 14 families were found. Among the collected material, 7 species are new records for Iranian fauna: Cryptostemma (Pachycoleus) gracile Josifov 1967, Cryptostemma (Pachycoleus) utnapishtim Linnavuori 1984, Systelloderes utukhengal Linnavuori 1984, Phytocoris (Eckerleinius) paghmanus Linnavuori 1974, Himacerus (Himacerus) apterus (Fabricius 1798), Nabis (Dolichonabis) limbatus Dahlbom 1851 and Reduvius osiris Kirkaldy 1909.